Targeted photothrombotic subcortical small vessel occlusion using in vivo real-time fiber bundle endomicroscopy in mice - Kim, Minkyung; Choi, Won Seok; Moon, Hyuk June; Han, Sungmin; Shin, Hyun Joon (The Optical Society, 2023)
The development of an accurate subcortical small vessel occlusion model for pathophysiological studies of subcortical ischemic stroke is still insignificant. In this study, in vivo real-time fiber bundle endomicroscopy (FBE？) was applied to develop subcortical photothrombotic small vessel occlusion model in mice with minimal invasiveness. Our FBF？ system made it possible to precisely target specific blood vessels in deep brain and simultaneously observe the clot formation and blood flow blockage inside the target blood vessel during photochemical reactions. A fiber bundle probe was directly inserted into the anterior pretectal nucleus of the thalamus in brain of live mice to induce a targeted occlusion in small vessels. Then, targeted photothrombosis was performed using a patterned laser, observing the process through the dual-color fluorescence imaging. On day one post occlusion, infarct lesions are measured using TTC staining and post hoc histology. The results show that FBE？ applied to targeted photothrombosis can successfully generate a subcortical small vessel occlusion model for lacunar stroke.